Empathy and Aesthetics: Edvard Munch and the Paradox of Pictorial Thinking - Gustav Jørgen Pedersen (Kunst og Kultur)
The article investigates the relationship between empathy and aesthetics from a dual perspective. First, I discuss a painting by the Norwegian painter Edvard Munch, Weeping Nude [Gråtende akt] (1913–14), through the lens of 19th century theories on aesthetic empathy, primarily as formulated by Theodor Lipps and Robert Vischer. And second, I reverse the point of view in order to discuss empathy and aesthetics through the lens of what I call the paradoxical pictorial thought of Munch’s paintings. In contrast to the 19th century theories on aesthetic empathy, which I argue presuppose the distinct separation between subjectivity (interiority) and objectivity (exteriority), I contend that Munch’s paintings articulate how the affective dimension of our being is not private, and interior, but something that is sharable prior to the subject–object division.